(untitled) (Південний архів (історичні науки), 2022)
Purpose and methodology of work. The study of public activity of the Odessa Jewish Society requires a comprehensive analysis of various aspects of its activities. Given the multifaceted, diverse form of activity of the Jewish Society of Odessa, the analysis of the development of Jewish participation in urban self-government, education of farms is an important aspect in the study of the general situation in Odessa. Research of public activity of the Odessa society in the outlined question is an important aspect at its detailed coverage. One of the aspects of the activities of this society in the late nineteenth – early twentieth century. became management, education and other aspects of Jewish life in Odessa. Analysis of the range of periodicals on the subject of the study will shed light on the situation of the Jewish population of Odessa. The study is based on source studies methods for identifying, analyzing and evaluating sources. Methods of historical research, in particular historical-comparative, are used, which were used to establish the range of newspaper sources needed to cover the topic. Results and scientific novelty of the study. A study of the public activities of the Odessa Jewish Society, allows us to conclude about the active activities of the Jewish Society in the field of governance, education, relations with Palestine in the late nineteenth – early twentieth century. The issue of Jewish participation in the city’s public administration is covered. It is told about the long-term fruitful work of the public Duma RL Harry. The election of Jewish vowels and their approval by the mayor are described. Some moments of the development of Jewish education in Odessa are analyzed. The names of institutions, the names of Jewish educators are given. The problems of Jewish educational institutions are listed. Anniversaries were celebrated, their activities and careers were told. The activity of the jubilee figure of the Jewish orphanage is described. The process of formation of the principle of distribution of loans among the settlements is shown. Two literary prizes are described in detail, their titles, cost, provisions, topics, sources of funding, deadlines. The work of the Society of Aid to Jewish Farmers in Palestine is shown. The facts from the life of Jewish farmers in Palestine and Syria are given. Their problems and achievements in the presentation of the agronomist of the society are described. The colonies of Jewish farmers are described in detail.